2014
DOI: 10.3389/fonc.2014.00227
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Impacts of Ascorbate on Human Metastatic Melanoma Cells

Abstract: In recent years, increasing evidence has emerged demonstrating that high-dose ascorbate bears cytotoxic effects on cancer cells in vitro and in vivo, making ascorbate a pro-oxidative drug that catalyzes hydrogen peroxide production in tissues instead of acting as a radical scavenger. This anticancer effect of ascorbate is hypoxia-inducible factor-1α- and O2-dependent. However, whether the intracellular mechanisms governing this effect are modulated by epigenetic phenomena remains unknown. We treated human mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 91 publications
2
30
0
1
Order By: Relevance
“…Compared to untreated tumor-bearing mice, we found a statistically significant increase in expression of gene p53 (p<0.02) in tumor-bearing mice treated with ascorbate. This is consistent with reports in the literature of ascorbate's effect on the p53 gene [30, 64,80]. Our data showed that p53 gene expression was elevated in ascorbate treated groups of mice with tumors, tended to decrease as tumors became larger and was reduced in animals with metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to untreated tumor-bearing mice, we found a statistically significant increase in expression of gene p53 (p<0.02) in tumor-bearing mice treated with ascorbate. This is consistent with reports in the literature of ascorbate's effect on the p53 gene [30, 64,80]. Our data showed that p53 gene expression was elevated in ascorbate treated groups of mice with tumors, tended to decrease as tumors became larger and was reduced in animals with metastatic tumors.…”
Section: Discussionsupporting
confidence: 93%
“…reverse transcriptase (TERT), which regulates telomere length, can promote tumor development, increases the anti-apoptotic capacity of cells, enhances DNA repair [77] and nuclear factor erythroid derived 2 (Nrf2), which has anti-apoptotic effects and may therefore protect cancer cells [78][79]. Ascorbate has been shown to target the expression of these genes (promoting p53 while inhibition expression of the others) in tumor cells [57][58][59]80], which in turn shifts cells toward the sub-G1 fraction.…”
Section: Introductionmentioning
confidence: 99%
“…An epochal event is taking place in cancer treatment, but the misunderstanding is always in ambush! The Authors of a related article [84] conclude: "… Pauling may have been correct on the use of high doses of Vitamin C for cancer therapy, but for wrong reasons -not as an antioxidant, but as a pro oxidant anticancer agent"; knowing the real story of Vitamin C, one can easily realize that this is simply not true! Pauling never considered the anti-or pro-oxidant properties of ascorbate; he rather pointed out its effects as a booster of the immune response!…”
Section: Resultsmentioning
confidence: 99%
“…• It improves the quality of life of cancer patients [72] • It prolongs their survival [26,27,73] • It potentiates the cytotoxic effects and reduces the side effects of conventional chemotherapy [74] • It is remarkably safe in both physiologic, and pharmacologic concentrations [75] • It boosts the immune response, in cancer patients [76][77][78][79] • It increases the host resistance to neoplasia [80,81] • It protects against the development of neoplasia [82,83] • It is an epigenetic modulator of genes with a key role in cancer development [84,85] • It is highly cytotoxic in vitro against a number of different human tumor cell lines [30,31,[33][34][35][36] • It exert a powerful cytotoxic effect against colorectal cancer cells refractory to targeted therapies [86,87].…”
Section: Improving Ascorbate Treatment Of Cancermentioning
confidence: 99%
“…The role of DNMT1 is to ensure the inheritance of the DNA methylation pattern through cell division. Since aberrant expression of DNMT1 occurs in the majority of cancer types, DNA methylation-based biomarkers mediated by DNMT1 have been used as diagnostic tools, with modification typically occurring in the CpG-rich island of the gene promoter region (19)(20)(21). Therefore, it has been suggested that DNA methylation patterns may be used to distinguish cancer cells from normal cells (22).…”
Section: Discussionmentioning
confidence: 99%